Pregnant in the king's palace - Hunter, Kelly (Harlequin presents, 2021)
The woman who could cost him his crown...or save it! Rumours abound that our beloved king, Valentine, is abdicating! His reasons are unknown, although speculation is that he cannot provide our kingdom with an heir. The eyes of the world are on him, yet our rebellious royal has eyes only for enchanting Angelique, horse trainer to the elite... Their attraction is as potent now as it was ten years ago, when they first met! We thought Valentine's abdication was his biggest scandal...but given their fiery reunion, could passionate, headstrong Angelique be carrying an even more shocking secret?